2016
DOI: 10.1039/c6ra08776k
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and biomimetic total synthesis of tomentodiones A–B, terpenoid-conjugated phloroglucinols from the leaves of Rhodomyrtus tomentosa

Abstract: Tomentodiones A (1) and B (2), a pair of C-11′ epimers of caryophyllene-conjugated phloroglucinols with an unprecedented skeleton, were isolated from the leaves of Rhodomyrtus tomentosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The NOE correlations between H-9 and H 3 -12 as well as H-1 and H 3 -13/H-5 indicated that the cyclobutane ring was trans-fused with the nine-member ring. Additionally, the relative configuration of the sesquiterpoid moiety of 1 (1a) could be further corroborated by comparison of the NMR data with the known meroterpenoids 2 and 3 [11,14,16]. Moreover, cross peaks between H 3 -14 and H-8′/H-6, between H-5 and H-7′ indicated that the sesquiterpenoid moiety was trans-fused with the dihydropyran ring ( Figure 3).…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…The NOE correlations between H-9 and H 3 -12 as well as H-1 and H 3 -13/H-5 indicated that the cyclobutane ring was trans-fused with the nine-member ring. Additionally, the relative configuration of the sesquiterpoid moiety of 1 (1a) could be further corroborated by comparison of the NMR data with the known meroterpenoids 2 and 3 [11,14,16]. Moreover, cross peaks between H 3 -14 and H-8′/H-6, between H-5 and H-7′ indicated that the sesquiterpenoid moiety was trans-fused with the dihydropyran ring ( Figure 3).…”
Section: Resultsmentioning
confidence: 74%
“…The four known compounds were identified as myrtucommulone K (2) [16], tomentodione B (3) [11], tomentodione C (4) [14] and tomentosenol A (5) [13], respectively, by comparison of their spectral data with those reported in the literatures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is recommended that more detailed study such as deep and systematic phytochemical investigation and its mechanism of toxicity action to be carried out on the extracts of this study to figure out what caused the difference in cytotoxicity displayed by the leaves and root extract of the plant. In recent years, there are considerable phytochemical studies aimed at exploring the relatively unknown R. tomentosa leaves and have resulted in the isolation of several unique phloroglucinols which are all novel to science (Hiranrat and Mahabusarakam, 2008;Liu et al, 2016). However, their cytotoxicity is yet to be tested and more can be done in the future to determine their bioactivities.…”
Section: Cytotoxicity Propertiesmentioning
confidence: 99%